2005
DOI: 10.7824/rbh.v4i2.30
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de herbicidas aplicados na pré-colheita na qualidade fisiológica das sementes de feijão

Abstract: One of the strategies to improve the mechanic harvest performance is using desiccants in pre-harvest application. Thus, an experiment was carried at "Fundação ABC" experimental area during 2001/2002 season, in Arapoti, Parana State, Brazil. The aim of the study was to evaluate the pre-harvest desiccants effect on common bean seeds quality (germination and vigor) after harvest and after a period of 8 month of storage. The variety Carioca under no tillage system was used. The treatments were applied using a pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Opposites results were verified when evaluating the effect of herbicides applied in preharvest of soybean, where the ammonium glufosinate (300 g a.i. ha -1 ) did not affect the germination and the vigor of the seeds (Penckowski et al, 2005).…”
Section: Resultsmentioning
confidence: 78%
“…Opposites results were verified when evaluating the effect of herbicides applied in preharvest of soybean, where the ammonium glufosinate (300 g a.i. ha -1 ) did not affect the germination and the vigor of the seeds (Penckowski et al, 2005).…”
Section: Resultsmentioning
confidence: 78%
“…However, several studies have reported negative effects of this herbicide, when it is used for desiccation of soybeans between stages R6 and R7.2, on physiological seed quality and early seedling performance, especially on the seedling root system (Daltro et al, 2010;Guimarães et al, 2012). Penckowski et al (2005), while assessing the effect of pre-harvest desiccation on bean seed quality, observed that treatments with glufosinateammonium + etephon, diquat and glufosinate-ammonium were efficient in desiccating the crop and did not affect germination and vigor, but paraquat (240 g a.i.ha -1 ) and glyphosate (720 g a.i.ha -1 ) were not as efficient as the other treatments, and negatively affected germination. Glyphosate also reduced seed vigor.…”
Section: Introductionmentioning
confidence: 99%
“…The herbicide active ingredient can affect the compositional quality and physiological performance of seeds during propagation, reducing the seed germination rate and field vigor. In common beans, for example, Penckowski et al [80] found that ammonium glufosinate (120 to 480 g ha −1 of active ingredient) and ethephon (100 to 400 g ha −1 of active ingredient), diquat (300 to 600 g ha −1 of active ingredient), and ammonium glufosinate (300 g ha −1 of active ingredient) applied as crop desiccants did not affect the common bean germination rate and field vigor; however, paraquat and glyphosate negatively affected the common bean germination rate, and glyphosate also reduced the common bean seed vigor.…”
Section: Crop Desiccation As a Crop Management Toolmentioning
confidence: 99%